2022
DOI: 10.1111/prd.12419
|View full text |Cite
|
Sign up to set email alerts
|

Oral health‐related quality of life of patients rehabilitated with fixed and removable implant‐supported dental prostheses

Abstract: Oral health-related quality of life is an established and relevant instrument with which to describe patient satisfaction. It was developed with a psychometric and social survey background and encompasses multiple dimensions of life, ranging from impairment

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
79
1
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(86 citation statements)
references
References 88 publications
1
79
1
5
Order By: Relevance
“…However, reimplantation was commonly associated with ridge augmentation or sinus grafting procedures. [38][39][40][41][42][43][44][45][46][47] When reconsidering the treatment plan following implant loss, it is apparent that implant therapy may not necessarily improve oral health-related quality of life relative to conventional restorations, as critically appraised in the review paper by Duong et al 50…”
Section: Impl Ant Removal and Prepar Ati On Of The " Ne X T Round"mentioning
confidence: 99%
See 1 more Smart Citation
“…However, reimplantation was commonly associated with ridge augmentation or sinus grafting procedures. [38][39][40][41][42][43][44][45][46][47] When reconsidering the treatment plan following implant loss, it is apparent that implant therapy may not necessarily improve oral health-related quality of life relative to conventional restorations, as critically appraised in the review paper by Duong et al 50…”
Section: Impl Ant Removal and Prepar Ati On Of The " Ne X T Round"mentioning
confidence: 99%
“…When reconsidering the treatment plan following implant loss, it is apparent that implant therapy may not necessarily improve oral health–related quality of life relative to conventional restorations, as critically appraised in the review paper by Duong et al 50 …”
Section: Implant Removal and Preparation Of The “Next Round”mentioning
confidence: 99%
“…In general, the changing demographics and aging of the population have increased the proportion of patients aged over 70 years who have medically multi-morbid disease involvement [54]. This has a direct impact on dentistry as well, and especially on the discipline of reconstructive dentistry: (1) tooth loss occurs at higher ages resulting in more complex prosthetic treatment; (2) older individuals have worse acceptance of (removable) prostheses; and (3) there is a higher risk of supplementary implants in medically compromised patients [55,56]. For these reasons, it is obvious that networking with general medicine, and in particular with geriatrics, will become increasingly important for the prosthodontist in the future to deliver personalized workflows in reconstructive dentistry.…”
Section: Demographic Developmentmentioning
confidence: 99%
“…As gold alloy has the longest history of use in metalceramic constructions, most long-term studies investigate gold alloy [3][4][5][6][7][8][9]. A survey conducted among prosthodontists showed that the most used material for tooth-supported short-and long-span fixed dental prostheses (FDPs) is porcelain-veneered cobalt-chromium (CoCr) [1].…”
Section: Introductionmentioning
confidence: 99%